Kualitas Sensoris Telur Pindang batik yang Disamak dengan Teh Hitam: Sensory Qualities of Pindang batik Eggs Tanned with Black Tea (Jurnal Riset Agribisnis dan Peternakan, 2024)
The purpose of this study was to determine the effect of tea leaf levels as a tanner on pindang batik egg organoleptic tests. The results of this study are expected to be useful as information for producers about the level of tea leaves as a tanning agent for organoleptic tests of pindang batik eggs.      There is an influence of tea leaf levels as a tanner on the organoleptic test of pindang batik eggs.  The material in this study was chicken eggs, tea leaves, salt, water and garlic. The study used was an experiment with a complete randomized design. The results of the analysis of the various effects of tea leaf levels as a tanner for pindang batik eggs showed no real difference (P>0.05) against the organoleptic test of pindang batik egg taste.  The results of variety analysis showed a significant difference (P0.05) from the organoleptic test of pindang batik egg yolk color.  The results of variety analysis did not show a noticeable difference (P>0.05) against the organoleptic test of pindang batik egg odor. The results of the analysis of pindang batik egg variety showed a real difference (P
Keywords: Egg; Batik Pindang; Organoleptic; Black Tea